2014
DOI: 10.1016/j.jpcs.2014.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Field-effect switching in nano-graphite films

Abstract: The effect of electrical resistivity switching in nano -graphite films is described. In difference with cases published elsewhere the switching in nano -graphite films occurs from stable high conductive to metastable low conductive state. Critical current of switching varies in the range 0.01-0.5A and can be increased up to values appropriate for using of nano -graphite samples in power grids as contact-less current limiters and circuit breakers. The possible mechanisms of switching phenomenon in nano -graphit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 25 publications
3
7
0
1
Order By: Relevance
“…Instead, all our results can be accounted for by considering the pre-existence of superconducting-prone islands in graphite, consistently with previous reports in the literature indicating localized superconducting domains in the material [16,12,14,15,35]. In this context, the presence of superconducting leads can act as a trigger for global coherent transport along such pre-existing channel.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Instead, all our results can be accounted for by considering the pre-existence of superconducting-prone islands in graphite, consistently with previous reports in the literature indicating localized superconducting domains in the material [16,12,14,15,35]. In this context, the presence of superconducting leads can act as a trigger for global coherent transport along such pre-existing channel.…”
Section: Discussionsupporting
confidence: 91%
“…This can be justified by considering the superconducting islands in graphite as objects with reduced dimensions (as suggested from STM, magnetization and transport measurements in different types of pristine graphite [16,12,14,15,27],…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Хотя переходы «металл -диэлектрик» в графите [26][27] и в неупорядоченном углероде [28][29] хорошо известны, однако до сих пор перехода в состояние диэлектрика в НГ-пленках выше комнатной температуры не обнаружено. Более подробное обсуждение гипотезы сверхпроводимости в НГ-пленках можно найти в работе [30]. Заключение В статье описан вероятный механизм переключения электросопротивления в НГ-пленках.…”
Section: Discussionunclassified
“…Studies of nanographite films carried out for 30 years [7][8][9][10][11][12] demonstrated the presence of the so-called " weak superconductivity" at room temperature and even higher up to 650 K (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%